The usefulness of a simple field test to evaluate lower limb muscle endurance in baseball pitchers - Shimizu, C.; Nakagaki, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2021)
The purpose of this study were: 1) to investigate the relationship between lower limb muscle endurance and the rate of decrease ball velocity in baseball pitchers, and 2) to propose a simple field test (FT) to evaluate the lower limb muscle endurance. The eight collegiate baseball pitchers were participated in this study. The rate of change in ball velocity when a pitcher threw 50 consecutive balls (every 12 seconds) was defined as the rate of decrease in ball velocity. The muscle endurance of flexion and extension of the hip and knee joints was measured using an isokinetic dynamometer device. The number of repeated back-range to exhaustion was used as the endurance of the lower limb muscles obtained from FT. The rate of decrease in ball velocity was significantly correlated with isokinetic muscle endurance in knee flexion and the number of repetitions of the back-lunge. The number of repetitions of back-lunge was significantly correlated with isokinetic muscle endurance of knee flexion. These results suggest that 1) pitchers with a low rate of decrease ball velocity have superior muscular endurance in knee flexion, and 2) the FT proposed in this study is useful as a simple test to evaluate the muscular endurance in knee flexion related to the rate of decrease ball velocity.